Application of the Chromosome Image Analyzing System (CHIAS) for Straightening Cation‐treated Bent Chromosomes. Issue 11 (10th July 2020) - Dwiranti, Astari; Arifudin, Fendi Sofyan; Takata, Hideaki; Ohmido, Nobuko; Fukui, Kiichi
Abstract: Divalent cations, mainly calcium and magnesium ions, are known to play a major role in the maintenance of chromosomes. The depletion of both ions using ethylenediaminetetraacetic acid (EDTA) results in a bent chromosome structure with extended arms and dispersed chromatin fibers. The importance of divalent cations for the maintenance of chromosome structure has been reported previously; nevertheless, previous studies were limited to qualitative data only. Straightening the bent image of the chromosome would provide quantitative data. Thus, this study aimed to evaluate the effects of cation depletion by the application of the Chromosome Image Analyzing System (CHIAS) to straighten bent chromosomes. Human HeLa chromosomes were treated with EDTA as a known chelating agent in order to investigate the importance of divalent cations on the maintenance of chromosome structure. Chromosomes were stained and directly observed with a fluorescence microscope. Images were then analyzed using CHIAS. The results revealed that EDTA‐treated chromosomes showed longer arms than those without EDTA treatment, and most of them tended to bend‐out. By straightening the image using CHIAS, the bent chromosomes were successfully straightened. The average lengths of the chromosomes treated with and without EDTA were 4.97 and 0.96 μm, respectively. These results signify the advantages of CHIAS for chromosome analysis and highlight the fundamental effects of cations on chromosome condensation. Abstract : Chromosomes treated with EDTA showed long and bent‐out arms. Using CHIAS, the bent chromosome images were successfully straightened. These results signify the advantages of CHIAS and reveal the major effect of cations on chromosome structure.